DEGRADABLE PACKAGING MATERIALS – SOURCES, APPLICATION AND DECOMPOSITION ROUTES - Šuput, Danijela; Popović, Senka; Hromiš, Nevena; Ugarković, Jovana (Journal on Processing and Energy in Agriculture, 2021)
There are many biodegradable and recyclable packaging materials available, alternatives for plastics: paper and cardboard; biodegradable polyethene (degradagle due to additive incorporated during production, whose role is to lead to the polyethylene break down into CO2, H2O, biomass and minerals when in landfill) and biodegradable plastic (made from renewable biomass-biopolymers in a relatively energy efficient process). The decomposition routes of degradable materials are reflected in the degradation for which realization a physico-chemical stimulus is required and biodegradation for which microorganisms are responsible. The global biodegradable plastic market was valued at 1.6 billion in 2019 and it is expected to reach 4.2 billion by 2027. The largest segment by application of biodegradable materials is in packaging with a market share of more than 60%. Some examples of degradable packaging existing on the market will be presented in the paper.